MODEL PENATAGUNAAN TANAH DI INDONESIA BERDASARKAN UNDANG UNDANG NOMOR 5 TAHUN 1960 - TOTOK DWINUR HARYANTO (Wacana Hukum, 2009)
Abstract: Land, water and all treasures in it are the source for people wealth. Therefore, we need to control its usage. The land usage as a chain of controlling, supplying and distribution in a well planned activity are used to give wealth to people. There are three models of it, namely closed (zoning) opened and the usage that aims at serving to the development. Indonesia applies three of them. Keyword: land usage models